Roundtable on Sustainable Palm Oil Certification: Advancing Sustainability through Phenomenology Studies of Transcendent Auditing Practices - Andi Irfan; Iwan Triyuwono; Ali Djamhuri; Aji Dedi Mulawarman (Universitas Pasundan, 2024)
This research focuses on the examination of the Roundtable on Sustainable Palm Oil (RSPO) certification, which strives to save the environment while maintaining the economic advantages of palm oil plants by using sustainable methods. The research technique used in this study include conducting interviews and focus group discussions with stakeholders engaged in the RSPO audit, as well as evaluating data from the RSPO website in conjunction with up-to-date academic literature. The results indicate that several principles confirmed in the RSPO audit are in accordance with transcendent ideals included in the Quran. These principles specifically address the negative impact on the environment, as described in Q.S Ar-Rum 42, which states: